Wujud Citraan pada Novel Kata Karya Rintik Sedu - Hestiaty, Hestiaty; Rimang, Siti Suwadah; Alawi, Nurhidayat Alip; Ardianto, Agus (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2024)
The Form of Imagery in the Novel Kata by Rintik Sedu. (supervised by Ita Suryaningsih and Fitrawahyudi) This research is qualitative research which aims to identify the form of imagery contained in the novel Kata. This research uses a qualitative descriptive data analysis method. The data source in this research is the entire content of the novel Kata. The techniques used in collecting data are (1) Library technique, which is a technique that uses written sources to obtain data, (2) Listening technique, by reading the novel entitled Kata by Rintik Sedu carefully and thoroughly so that the aims and objectives of the novel what is researched can be explained well, (3) Note-taking technique, this recording is done using a writing instrument or with the help of a computer. The data analysis technique used in this research uses the analysis model according to Milles and Huberman which includes four components, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, the forms of imagery used in the novel entitled Kata by Rintik Sedu are images of sight, hearing, movement, touch and smell. The results of the research found a total of two hundred and nineteen data which was divided into ninety-one data on visual imagery, thirteen data on auditory imagery, sixty-six data on movement imagery, forty-eight data on tactile imagery, and one data on olfactory imagery. It can be concluded that the novel Kata has various forms of imagery.